PENERAPAN MANAJEMEN RISIKO KREDIT PADA KPR BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN - Arsya Ghefira (2022)
The consumptive needs of the community in buying houses by utilizing sources of funds from banks or known as KPR at Bank Pembangunan Daerah Jawa Barat and Banten are increasing every year, even though in 2021 there will be a Covid-19 pandemic situation. The banking industry compared to other industries has a high risk, credit risk is the biggest risk experienced by the Bank. Credit risk can occur when the debtor is unable to complete the payment in accordance with the agreed time period. In implementing risk management, each bank has its own methods and strategies. This final project aims to determine the process of implementing credit risk management on mortgages at Bank Pembangunan Daerah Jawa Barat and Banten and to find out how to apply credit risk management in minimizing non-performing loans at Bank Pembangunan Daerah. West Java and Banten. This discussion uses a qualitative descriptive method, namely by utilizing qualitative data in the annual report of Bank Pembangunan Daerah Jawa Barat and Banten and using descriptive. The results of this final project also show that the application of credit risk management at Bank Pembangunan Daerah Jawa Barat and Banten, has been implemented well and can be seen from the non-performing loans in 2021 which experienced the best decline since 2017.